Immune Tolerance in Mytilus galloprovincialis Hemocytes After Repeated Contact With Vibrio splendidus - Rey-Campos, Magalí; Moreira, Rebeca; Gerdol, Marco; Pallavicini, Alberto; Novoa, Beatriz; Figueras, Antonio (Frontiers in Immunology, 2019)
Mediterranean mussels (Mytilus galloprovincialis) are sessile filter feeders that live in close contact with numerous marine microorganisms. As is the case in all invertebrates, mussels lack an adaptive immune system, but they respond to pathogens, injuries or environmental stress in a very efficient manner. However, it is not known if they are able to modify their immune response when they reencounter the same pathogen. In this work, we studied the transcriptomic response of mussel haemocytes before and after two consecutive sublethal challenges with Vibrio splendidus. The first exposure significantly regulated genes related to inflammation, migration and response to bacteria. However, after the second exposure, the differentially expressed genes were related to the control and inhibition of ROS production and the resolution of the inflammatory response. Our results also show that the second injection with V. splendidus led to changes at the transcriptional (control of the expression of pro-inflammatory transcripts), cellular (shift in the haemocyte population distribution) and functional levels (inhibition of ROS production). These results suggest that a modified immune response after the second challenge allowed the mussels to tolerate rather than fight the infection, which minimized tissue damage.